2021
DOI: 10.5219/1508
|View full text |Cite
|
Sign up to set email alerts
|

The influence of yeast extract and jasmonic acid on phenolic acids content of in vitro hairy root cultures of Orthosiphon aristatus

Abstract: Phenolic acids represent a big group of plant secondary metabolites that can be used as food additives, nutraceuticals, and pharmaceuticals. Obtaining phenolic acids from the plant in vitro cultures provide an attractive alternative to produce high-value plant-derived products. The impact of yeast extract and jasmonic acid on the induction of defense responses and consequently the production of phenolic acids in vitro hairy root cultures of  O. aristatus have been investigated.  Treatment of O. aristatus cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 47 publications
0
13
0
1
Order By: Relevance
“…Therefore, such concentration was recommended for the fabrication of sausage meat mixes. Scientific works [34], [35], [36], [37] describe studies using different concentrations of the table and sea salts in the range from 0.5 -1.5%; as a result of similar studies, it was found that such concentrations hurt the organoleptic properties of the finished product. The one more recommendation was to enrich them with iodine, preferably by the extract of laminaria to compensate its deficit, what technique is the best recommended for use [38], [39], [40], [41].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, such concentration was recommended for the fabrication of sausage meat mixes. Scientific works [34], [35], [36], [37] describe studies using different concentrations of the table and sea salts in the range from 0.5 -1.5%; as a result of similar studies, it was found that such concentrations hurt the organoleptic properties of the finished product. The one more recommendation was to enrich them with iodine, preferably by the extract of laminaria to compensate its deficit, what technique is the best recommended for use [38], [39], [40], [41].…”
Section: Resultsmentioning
confidence: 99%
“…YE does not have a constant composition and is a mixture of compounds including amino acids, vitamins and minerals and various unknown compounds, which makes it difficult to determine its possible mode of action [ 27 ]. However, many studies indicate that YE has an effect on the secondary metabolism of Lamiaceae family members [ 23 , 28 , 29 ]. As abiotic elicitors, MJA and cadmium ions were selected, as most reports of RA elicitation concern the effect of jasmonate derivatives and heavy metal salts [ 23 , 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Reducing humidity and increasing porosity can reduce energy consumption for further drying, which can significantly speed up the process, simplify the selection and maintenance of the dryer [22], [23], [24]. The driving force of the dehumidification process is increased by vibration extrusion, centrifugation during rotor spinning, development of an electroosmotic effect when creating conditions for unilateral diffusion, and the process of filtering the medium through the perforation of the rotor.…”
Section: Scientific Work [7] [8] [9] [10]mentioning
confidence: 99%